Father-child discourse in Family Guy: a corpus-based analysis - Anhelina Sliepushova (Синопсис: текст, контекст, медіа, 2020)
The article aims at analysis of gender and family stereotypes in father-child communication in an animated series Family Guy, featuring a typical American family. The study focuses on Peter Griffin's discourse, the father of the family, containing his communication with two of his teenage children, a son and a daughter, unveiling gender peculiarities in father-son and  father-daughter discourses. The attempt is made to disclose how gender and family roles are verbalized in communication between family members. The conversation, discourse and corpus-based analyses have been used to analyze the main character's discourse in order to single out the father's specific vocabulary — through word lists, keyword lists, clusters and collocations — he uses while communicating with his son and daughter. The findings show that Peter Griffin chooses different language means while talking to his son and daughter. Thus, his discourse addressing his adolescent son Chris is rich in direct addresses, mainly commands when the father tries to discipline his son. Offering his son emotional support or encouragement the father stays forthright with him creating an image of “real men” stereotypical conversations. On the contrary, while communicating with his daughter Peter modifies her name Meg addressing her as honey, sweetheart, one-of-a-kind in father-daughter discourse. However, using diminutives he humiliates his daughter and makes her feel an abandoned child. In this way, he makes her feel special but in a negative way. Family communication created in the animated series reflects gender stereotypes in father's attitude to his children belonging to two different sexes. Nevertheless, this verbal tendency does not affect relationships within the family. For the future, it is worthwhile to compile a larger corpus including mother-child, child-father, and child-mother discourses to get more representative results.